APLIKASI MESIN EXTRUDER KAWAT UNTUK MENINGKATKAN PRODUKTIFITAS PERAJIN PERAK “DHIMAS SILVER” DESA UNGGA, KECAMATAN PRAYA BARAT DAYA, KABUPATEN LOMBOK TENGAH - Suartika, I Made; Wijana, Made; Putra, I Nyoman Nugraha Ardana; Joniarta, I Wayan; Ramadhan, Galang Baruna; Putra, Ardi Wijaya (Jurnal Abdi Insani, 2025)
PBM-PKM's partner in this activity is Dhimas Silver with the owner Mr. Sarinda Farid Risky. The partner location is in Ungga Village, Southwest Praya District, Central Lombok. Featured products are: brooches, rings, studs, hairpins, suweng (a type of stud), pendants, bracelets and brooches-pendants. The jewelry is made from a combination of pearl shells which are shaped into oval, round, oval, rectangular, triangular and half round shapes and then framed with silver ornaments combined with pearls to produce classy handicraft products. The problem for SMEs in the production sector is the difficulty in making wire sizes smaller than 0.5 mm, so partners want help in making extruder style wire drawing machines. The aim of this activity is to solve production problems in making wire. The solution for the production sector was to create a wire pulling machine. The results of the activity produced a wire drawing machine with an extruder type. Wire pulling machine specifications Frame/chassis size Length 71.5 cm Width 51.5 cm Height 80 cm, angle iron 2 mm thick 5 x 5 cm. The driving electric motor is ¾ HP, 1400 rpm pulley Ǿ 3 inch connected to a V belt to the middle pulley (input gear box) Ǿ 7 inch with a transmission ratio so that the input gear box rotation is 600 rpm. The rotation of the input gear box in the middle rack will be reduced by the gear ratio 1:50 so that the output rotation of the gear box is 12 rpm, the output rotation of the gear box will be transmitted to the wire pulling roller on the top shelf using a v belt pulley system, with a diameter ratio Ǿ 3 inch to Ǿ 7 inch so that the rotation of the wire pulling roller becomes 5.5 rpm